Paediatricians' knowledge, attitudes and practice following provision of educational resources about prevention of prenatal alcohol exposure and Fetal Alcohol Spectrum Disorder - Payne, J.; France, K.; Henley, N.; D'antoine, Heather; Bartu, Anne; Mutch, R.; Elliott, E.; Bower, C. (Blackwell Scientific Publications, 2011)
Aim: The study aims to provide paediatricians in Western Australia (WA) with educational resources (http://www.ichr.uwa.edu.au/alcoholandpregnancy) about the prevention of prenatal alcohol exposure and fetal alcohol spectrum disorder, and assess changes in their knowledge, attitudes and practice about fetal alcohol syndrome (FAS) and alcohol consumption in pregnancy. Methods: Following our 2004 survey of paediatricians, we developed and distributed educational resources to 159 paediatricians in WA in 2007. Six months later, we surveyed these paediatricians and compared their responses with results from 2004 using prevalence rate ratios (PRRs) and 95% confidence intervals (CIs).Results: Of 133 eligible paediatricians, 82 (61.7%) responded: 65.9% had seen the resources, of these 66.7% had used them and 29.6% said the resources had helped them change, or influenced their intent to change, their practice. There was no change in the proportion that knew all the essential features of FAS (18.3% in 2007; 20.0% in 2004) or had diagnosed FAS (58.5% in 2007; 58.9% in 2004). An increased proportion (75.6% in 2007; 48.9% in 2004) agreed that pregnant women should completely abstain from consuming alcohol (PRR 1.55, 95% CI 1.21–1.97). Only 21.7% (no increase from 2004) routinely asked about alcohol use when taking a pregnancy history. Conclusions: We recommend that asking about alcohol use during pregnancy should be emphasised in paediatric training. Unless paediatricians' capacity to ask about alcohol consumption when taking a pregnancy history and to diagnose FAS is increased, FAS will remain under-diagnosed in Australia and opportunities for management, early intervention and prevention will be overlooked.